Quantitative evaluation of the pH profile in organic acid fermentations - D.G. Hatzinikolaou; HY Wang (Biotechnology and Bioengineering, 1991)
One of the most important considerations in designing an integrated process for the production of organic acids is the strong pH dependence of the process parameters. The release of the acidic products during the fermentation alters the pH of the broth and subsequently affects the kinetics of cell growth and product formation. In addition, some parameters (such as the distribution coefficient of the products during extraction, their solubility constants during precipitation, etc.) in the subsequent separation processes following fermentation are also strong functions of pH. A pH profile predicting model for organic acids fermentation could be used in combination with specific separation process equations, in order to perform simulations concerning the feasibility of the whole process or the evaluation of the system's performance. In this work, such a general pH profile predicting model has been developed. The model requires knowledge of the fermentation medium composition and the kinetics of cell growth and product formation. The model has been verified for (but by no means restricted to) the case of butyric acid fermentation.